Pengaruh Terpaan Promosi Reksadana dan Terpaan Komunikasi Keluarga mengenai Keuangan terhadap Minat Berinvestasi Reksadana - Amrina Rida Hapsari; Tandiyo Pradekso (Interaksi Online, 2021)
This study aimed to determine the effect of reksadana (mutual fund) promotional exposure and family financial communication exposure on investment intention in reksadana (mutual fund). This study used quantitative-explanative research methods. The data collection used non-probability sampling with a total sample 50 respondents. The theory used are Cognitive Response Approach and Reference Group Theory. Data analysis for the hypothesis used simple linear regression analysis. Results of the analysis showed that the reksadana promotional exposure variable had 0.000 of significance value, so that means there is an effect of reksadana promotional exposure (X1) on investment intention in reksadana (Y). While the results of the analysis showed that family financial communication exposure variable had 0.190 of significance value, that means there is no effect of family financial communication exposure (X2) on investment intention in reksadana (Y).